The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jtcvs.2017.02.073
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics simulation of the right subclavian artery cannulation

Abstract: Right subclavian artery cannulation was cerebroprotective, especially on the right side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Our methods of computational analyses have been previously described. [7][8][9][10][18][19][20] Data for the analyses were acquired by electrocardiogram-gated 320-slice CT imaging. The image data in Digital Imaging and Communications in Medicine format were rendered into three-dimensional patient-specific geometries, including the aorta, coronary arteries, cervical branch arteries, and LVAD outflow graft using a dedicated software (AZE, Tokyo, Japan).…”
Section: Cfd Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our methods of computational analyses have been previously described. [7][8][9][10][18][19][20] Data for the analyses were acquired by electrocardiogram-gated 320-slice CT imaging. The image data in Digital Imaging and Communications in Medicine format were rendered into three-dimensional patient-specific geometries, including the aorta, coronary arteries, cervical branch arteries, and LVAD outflow graft using a dedicated software (AZE, Tokyo, Japan).…”
Section: Cfd Simulationsmentioning
confidence: 99%
“…5 Computational fluid dynamics (CFD) could help visualize and evaluate the blood flow, flow velocity, wall shear stress, and other fluid dynamic parameters in the three-dimensional aorta. [7][8][9][10] However, previous studies using CFD have only reported blood flow analysis in the ascending aorta without the aortic root because of the complex anatomy of the aortic root and its components such as the aortic valve, coronary arteries, and Valsalva sinus. [11][12][13][14][15] To evaluate the three-dimensional blood flow in the aortic root, three-dimensional patient-specific geometries with accurate anatomy of the aortic root were reproduced using electrocardiogram-gated 320-slice computed tomographic (CT) images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we performed computerized virtual surgery based on CFD combined with 3D CG. The CFD method was based on our previous validation studies [4,5]. We used the data obtained from thin-slice, early-phase, enhanced multidetector-row CT imaging.…”
Section: Casementioning
confidence: 99%
“…Their report consequently confirmed that the incidence rate of right-hemisphere stroke was significantly lower in the right axillary artery cannulation group. Numata and colleagues 4 reported that the right subclavian artery cannulation was cerebroprotective with the use of computational fluid dynamics simulation. They showed that a retrograde flow of the brachiocephalic artery and an antegrade flow of the right common carotid artery were produced from the blood streamline from the right subclavian artery throughout the cardiac cycle.…”
mentioning
confidence: 99%